A survey on the use of outcome measures by musculoskeletal physiotherapist's in India. (February 2014) - Mehta, Swekha; Grafton, Kate
Abstract In recent times, there has been great pressure on physiotherapists to become accountable for their practices and to provide evidence for effectiveness of their treatment. Therefore, it has become necessary to integrate standardised outcome measures (OMs) into clinical practice and boost evidence-based practice. The aim of this study was to determine the extent of use of outcome measures among physiotherapists in India and to identify the commonly used measures. A survey was conducted using a questionnaire consisting of 23 closed-ended questions. It was administered face-to-face and via email to Indian physiotherapists working with musculoskeletal patients. The response rate was 54% (n = 81). The results indicated 80% of the respondents used OMs with impairment-based measures being the most commonly used. Education qualifications, years of work experience and workplace setting were not significantly associated with utilisation of OMs. Various benefits and barriers to use of OMs were also identified. The findings of this study give insight into possible changes that could be incorporated in clinical practice and educational system for developing a standardised level of assessing patients and to tailor future implementation strategies.